Kinematics and paleoseismology of the Vernon Fault, Marlborough Fault System, New Zealand: Implications for contractional fault bend deformation, earthquake triggering, and the record of Hikurangi subduction earthquakes. Issue 7 (30th June 2014) - Bartholomew, Timothy D.; Little, Timothy A.; Clark, Kate J.; Van Dissen, Russ; Barnes, Philip M.
Abstract The 40 km long Vernon Fault, in the Marlborough Fault System of New Zealand, is characterized by dextral slip with subordinate reverse slip and exhibits abrupt variations in strike of up to 90°. Onshore fieldwork, paleoseismic trenching, and offshore high‐frequency seismic reflection data are integrated together to identify the kinematics and paleoseismic history of three sections of the fault: (1) the NNE striking Vernon Hills section which branches off from the Awatere Fault; (2) the NE striking Big Lagoon section which borders Big Lagoon to the south and extends 9 km offshore to the east; and (3) the E‐W striking Wairau Basin section, which is entirely submarine. The Vernon Fault can be shown to have a dextral slip rate of 0.8–4.9 mm/yr with a preferred estimate of 0.9 mm/yr (on the Big Lagoon section). We infer that a further unrecognized 3–4 mm/yr of dextral slip has been accommodated off fault as a result of accumulated slip on small and/or blind reverse faults adjacent to a 6 km wide restraining bend in the main fault. The onshore and offshore paleoseismic records are in good agreement. These indicate three to five events at eight sites and a mean recurrence interval of 3.9 ± 1.2 ka over the past 16 kyr, with the last event taking place at 3.3 ka. Earthquakes on the Vernon Fault are responsible for <25% of the Holocene subsidence rate of Big Lagoon over the last 13 ka. Most of the subsidence of this lagoon has been the result of surface deformation related with southern Hikurangi megathrust earthquakes.